Ferroptosis: New Dawn for Overcoming the Cardio-Cerebrovascular Diseases - Luo, Meng-Yi; Su, Jian-Hui; Gong, Shao-Xin; Liang, Na; Huang, Wen-Qian; Chen, Wei; Wang, Ai-Ping; Tian, Ying (Frontiers in Cell and Developmental Biology, 2021)
The dynamic balance of cardiomyocytes and neurons is essential to maintain normal physiological functions of heart and brain. If redundant cells die in tissues, serious cardio-cerebrovascular diseases would occur such as hypertension, myocardial infarction and ischemic stroke. The regulation of cell death plays a role in promoting or alleviating cardio-cerebrovascular diseases. Ferroptosis is an iron-dependent new type of cell death that has been proved to occur in a variety of diseases. In this review, we focus on the critical role of ferroptosis and its regulatory mechanisms involved in cardio-cerebrovascular diseases, and discusses the important function of ferroptosis-related inhibitors, which will provide the potential targets and strategies for the prevention and treatment of cardio-cerebrovascular diseases.